Eribulin-induced liver dysfunction as a prognostic indicator of survival of metastatic breast cancer patients: a retrospective study. Issue 1 (December 2016) - Kobayashi, Takayuki; Tomomatsu, Jyunichi; Fukada, Ippei; Shibayama, Tomoko; Teruya, Natsuki; Ito, Yoshinori; Iwase, Takuji; Ohno, Shinji; Takahashi, Shunji
Abstract Background Eribulin is a non-taxane, microtubule dynamics inhibitor that increases survival of patients with metastatic breast cancer. Although eribulin is well tolerated in patients with heavily pretreated disease, eribulin-induced liver dysfunction (EILD) can occur, resulting in treatment modification and subsequent poor disease control. We aimed to clarify the effect of EILD on patient survival. Methods The medical records of 157 metastatic breast cancer patients treated with eribulin between July 2011 and November 2013 at Cancer Institute Hospital were retrospectively analyzed. EILD was defined as 1) an increase in alanine aminotransferase or aspartate aminotransferase levels >3 times the upper limit of normal, and/or 2) initiation of a liver-supporting oral drug therapy such as ursodeoxycholic acid or glycyron. Fatty liver was defined as a decrease in the liver-to-spleen attenuation ratio to <0.9 on a computed tomography scan. Results EILD occurred in 42 patients, including one patient for whom eribulin treatment was discontinued due to severe EILD. The patients who developed EILD had significantly higher body mass indices (BMIs) than those who did not develop EILD (24.5 vs. 21.5, respectively;P  < 0.0001), with no difference in the dose intensity of eribulin between the two groups (P  = 0.76). Interestingly, the patients with EILD exhibited significantly longer progression-free survival (PFS) and overall survival (OS) than those without EILD (P  = 0.010 andP  = 0.032, respectively). Similarly, among 80 patients without liver metastasis, 19 with EILD exhibited significantly longer PFS and OS than the others (P  = 0.0012 andP  = 0.044, respectively), and EILD was an independent prognostic factor of PFS (P  = 0.0079) in multivariate analysis. During eribulin treatment, 18 patients developed fatty liver, 11 of whom developed EILD, with a median BMI of 26.7. Conclusions Although EILD and fatty liver occurred at a relatively high frequency in our study, most of the patients did not experience severe adverse effects. Surprisingly, the development of EILD was positively associated with patient survival, especially in patients without liver metastases. EILD may be a clinically useful predictive biomarker of survival, but further studies are needed to confirm these findings in another cohort of patients.